Energy‐related influences on variation in breastfeeding duration among indigenous Maya women from Guatemala. Issue 4 (3rd November 2016) - McKerracher, Luseadra J.; Collard, Mark; Altman, Rachel M.; Sellen, Daniel; Nepomnaschy, Pablo A.
Abstract: Objectives: The causes of variation in breastfeeding duration in humans are poorly understood, but life history factors related to maternal energetics drive much of the variation in lactation duration in nonhuman animals. With this in mind, we investigated whether four energy‐related factors influence variation in breastfeeding duration in a non‐industrial human population: (1) mortality risk during mother's development (assessed via mother's adult height), (2) reliance on nutrient‐dense weaning foods, (3) access to and need for help with infant feeding and care ("allomaternal care"), and (4) maternal tradeoffs between current and future reproduction (measured via child's birth order). Materials and methods: The data pertain to 51 Kakchiquel‐speaking Maya mothers and 283 children from a village in rural Guatemala. We developed a linear mixed model to evaluate the relationships between breastfeeding duration and the energy‐related factors. Results: Duration of breastfeeding was associated with two of the energy‐related factors in the ways we predicted but not with the other two. Contrary to predictions, taller mothers breastfed for shorter periods and we found no evidence that weanling diet quality impacts breastfeeding duration. As predicted, women who had more help with infants breastfed for shorter periods, and later‐born infants breastfed longer than earlier‐born ones. Discussion: The results regarding allomaternal care suggest that help reduces mothers' lactation demands. The energy saved may be redirected to increasing fecundity or investment in other children. The birth order result suggests that children born to mothers nearing reproductive senescence receive higher levels of investment, which likely impacts children's fitness.